STRATEGY AND POLICY INCREASING HUMAN DEVELOPMENT INDEX OF MANGGARAI REGENCY 2016-2021 - Salesman, Frans; Tapung, Marianus Mantovanni; Setiawan, Leonadus Ino (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2018)
Abstract The Human Development Index (HDI) is a composite index: health indicators through life expectancy, education indicators through mean expectations and school length, and per capita real purchasing power. The HDI level of NTT province in 2016 is 63.13 points, and Manggarai District in the same year amounted to 61.87 points. When compared with the national HDI, HDI Kabupaten Manggarai is still low. Therefore, it is necessary to develop Manggarai HDM strategy and policy during 2016-2021.Purpose. Develop strategies and policies to improve the Human Development Index in Manggarai 2016-2021. Methods. Analyzing Data publication BPS East Nusa Tenggara and Manggarai District 2014-2016, health profile of Manggarai District. Qualitative data obtained from the FGD preparation of Medium Term Development Plan Manggarai District 2016-2021. 42 FGD participants 42 persons. Results. The development of economic, education and health development strategies and policies that can accelerate the growth of HDI in Manggarai district during 2016-2021. Conclusion.IPM in Manggarai district has been in the "moderate" group with 2014 figure of 60.08 points, 2015 by 60.87 points, and by 2016. The growth of HDI between 2015-2016 is 1.31% if using the reduction of shortfall, the growth of HDI in Manggarai is included in slow category because the acquisition rate is <1.70. Accelerating the growth of HDI is a hope for all parties. Therefore, effective strategies and policies are needed to boost the slow growth of HDI to accelerate by utilizing all available resources. Keywords: Human Development Index, Development Strategy